Macroalgal biochar synthesis and its implication on membrane fouling mitigation in fluidized bed membrane bioreactor for wastewater treatment. (May 2023) - Maaz, Muhammad; Aslam, Muhammad; Yasin, Muhammad; Khan, Asim Laeeq; Mushtaq, Azeem; Fazal, Tahir; Aljuwayid, Ahmed Muteb; Habila, Mohamed A.; Kim, Jeonghwan
Abstract: The intensification of biochar into fluidized bed membrane bioreactor was investigated to mitigate membrane fouling. Different biochars from algal biomass were produced and used as biomaterials for wastewater treatment. In this study, different macroalgal biochar was synthesized at different pyrolysis temperatures and characterized using Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), Brunauer Emmett-Teller (BET) and Fourier transform infrared spectroscopy (FTIR) techniques to implicate their effect on membrane fouling reduction in fluidized bed membrane bioreactor. The combined effect of macroalgal biochars and biocarriers with gas sparging was evaluated for fouling mitigation. Macroalgal biochar curtailed membrane fouling effectively at low gas sparging rate. Transmembrane pressure (TMP) was reduced to 0.053 bar; under the fluidization of biochar-650 and biocarriers with gas sparging; from 0.27 bar (gas sparging only). Combined effect of gas sparging, biocarriers and biochar-650 instigated 92.1% fouling reduction in comparative to gas sparging alone. Mechanical scouring driven by biocarriers could reduce fouling due to removing surface deposit of foulants from membrane surface effectively and biochar can efficiently adsorb foulants because of its active functional groups resulting in reduction of colloidal fouling. The addition of divalent ions (Ca 2+ ) further enhanced the fouling reduction in fluidized bed membrane bioreactor. Graphical abstract: Image 1 Highlights: Different microalgal biochars were synthesized and characterized using various techniques. Implications of biochars for fouling mitigation in fluidized bed membrane reactor were evaluated. Membrane fouling was examined by fluidizing biocarriers, different biochars with gas sparging. Combined effects of biochar, biocarriers, gas sparging and calcium ions were critically investigated. Fouling control by integrating hybrid approach at reduced gas rates leading to low energy need.